Rancang Bangun Media Ajar Implementasi Finger Print Pada Pintu Geser Perpustakaan - Abdul Tahir; Jasman Jasman; Irdam Irdam (Departement of Mathematics Education, 2023)
Library visitor data is one of the indicators for assessing the success of managing a library. The library manager must ensure that every visitor data is recorded properly, so that the information obtained from processing the data can be used as a basis for continuous improvement, therefore for this activity to run well, an accurate, effective and efficient visitor recording system is needed. This research was conducted to provide solutions related to the above problems by building a library visitor recording system with biometric identification using fingerprints. The method used in this study is an experimental method by designing, manufacturing and testing tools. This system is equipped with the use of sliding doors as security which will open if library visitors have gone through the fingerprint identification process. Testing is carried out in three parts, the first test is on the application, database, and connection to the fingerprint module. The second test is on the connection between the fingerprint and the driving motor and the third test is on the Arduino connection with sliding door movement and limit switch performance. The test results go well and the system can work to record automatically, open and close doors according to the settings that have been made.